Design And Operation Of The Circulating Fluid Bed Roaster System For The Syama Gold Deposit Project - W. P. Wood; S. A. Bunk (Society for Mining, Metallurgy & Exploration, 1996)
In the early 1980's BHP identified several potential gold deposits in West Africa. One of these deposits was located in Mali, near the village of Syama. As a result of extensive exploration activities, an oxide ore as well as an underlying sulphide ore was identified. After agreement with the government of Mali was reached the development of the deposit was undertaken. The plan for the development of the mine included the treatment of the oxide ore followed by the treatment of the underlying transition and sulphide ore. The development of the deposit was extremely aggressive. Following the approval of the project in early 1989, engineering was started, equipment purchased sitework was started, and the first ore was introduced in December of 1989. This was accomplished in spite of the difficulties of the site. These difficulties included: • remote site location without air or road or water access • no existing infrastructure including water, power, or communication • high health risks • limited construction and manufacturing support in West Africa The operation began with a conventional crushing/grind-ing/CIL/elution and electrowinning facility. The facility was designed to treat 2000 metric tonnes of ore per day. After startup in December of 1989, the operation was improved to the point that plant throughput was averaging nearly 3000 tpd and running at 92 to 93% availability.